Impacts of unemployment benefit program on job search duration: Evidence from Indonesia - Wongkaren, Turro Selrits; Saragih, Tarimantan Sanberto; Aninditya, Flora; Siregar, Chairina Hanum; Nugroho, Aditya Harin; Ramdoniah, Rihlah; Augustin, Eldest; Fitriani, Kania; Mahaganti, Fergie Stevi; Febriansyah, Maurizky (Economic Journal of Emerging Markets, 2024)
Purpose ― This study examines the impacts of the Unemployment Benefit Program (Jaminan Kehilangan Pekerjaan, JKP) on the duration of job search in Indonesia using internal data sourced from the Employment Social Security Administering Agency (Badan Penyelenggara Jaminan Sosial Tenaga Kerja, BPJS TK).Method ― The Regression Kinked Design (RKD) model and Ordinary Least Square (OLS) estimation method are used to analyze the data on laid-off workers who have received the JKP benefits.Findings ― On average, the JKP beneficiaries have a longer duration of job search than laid-off workers who do not receive benefits. An increase in the replacement rate of the JKP benefits is associated with an increased duration of both job search and benefit claims. The RKD plot indicates that a replacement rate lower than 45% may decrease the duration of benefit claims and job searches. Implication ― The results imply that the government should consider two potential options: (1) maintaining the current level of monetary benefits that leads to a longer job search duration; in other words, the program management must continue providing benefits for the maximum duration offered (up to 6 months), or, (2) reducing the monetary benefits, if BPJS TK aims to reduce the job duration. The results may change if a more robust labor market information system is available.Originality ― This study represents the first attempt to investigate the impact of the Unemployment Benefit Program (JKP) on job search duration in Indonesia. It might also be important to enrich the existing literature on the impact of similar programs in developing countries and countries with large populations.